Analyzing Product-Mix Change Decisions Based on Realized Demand Data and Operational Constraints an Application to the Iraqi State Company for Food Industries and Its Effect on Operational Value Maximization (Al-Mansour Journal, 2026)
The paper investigates the impacts of product-mix change decisions using the actual demand information and operational limitations on the optimization of the operational values of five food-industry firms in Iraq throughout 20152025. The analysis applies the operational indicators that are measurable to capture the intensity of the portfolio reallocation using Mix-Shift Index (PMIX_MSI), market-production mismatch using Realized Demand Gap Rate (RDG_RATE), bottleneck pressure using Constraint Utilization Rate (CU_RATE), as well as the operational quality of the chosen mix using the index of the Weighted Contribution Margin (WCM_IQDK), whereas the dependent variable is operationalized as Realized Operational Value (OV_IQD_BN). The tests of cross-section dependence point to a number of series co-moving across firms, in line with exposure to common shocks, and unit root tests of stationarity are considered based on dependent panel-appropriate unit root procedures. The paper then estimates an ARDL error-correction specification in order to capture short-run and long-run equilibrium effects. The findings show that increased bottleneck utilization and robust product-mix reallocation are linked to high long-run operational value, and continued experienced gaps in realized demand diminish value. The significant error-correction term provides a consistent long-run relationship and a systematic adjustment procedure towards equilibrium after the disturbance of demand or capacity. The study suggests building a cycle of realized-demand-driven product-mix review, the adoption of product selection and pricing based on the profits of the bottlenecks, and a small dashboard of mix, mismatch, and constraint indicators that will decrease demand gaps and enhance the results of operational value.
Keywords: Product-mix change; Realized demand; Bottleneck constrain; Operational value; Panel data.